Analisis Dampak Kebijakan PENG-6/SP/2024 terhadap Implementasi e-Tax Court di Pengadilan Pajak - Budi Mulia Kurniawan; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The mission of the Tax Court is to establish itself as an accessible judicial institution for all seekers of justice. On July 31, 2023, the Chairman of the Tax Court launched the e-Tax Court information system through the issuance of PER-1/PP/2023. The e-Tax Court has been operational for a year, however the rate of appeal and lawsuit submissions through the system has not yet reached 80%, as in October 2024, the rate was only 57.14%. The implementation of the e-Tax Court appears to be far from optimal, because there are still many taxpayers who appeal manually either directly to the Tax Court office of 25.53% and by post 17.51%. Based on monitoring and evaluation results, the Secretary of the Tax Court issued Announcement No. PENG-6/SP/2024 on October 30, 2024, which limited in-person submission services and redirected them to assistance services for electronic filings via the e-Tax Court. One month after the announcement, appeal and lawsuit submissions via the e-Tax Court increased significantly by 24.32%, reaching 81.46%. This study aims to identify the benefits perceived by taxpayers, evaluate the implementation trends of the e-Tax Court from January to April 2025, and analyze the policy’s impact on the achievement of e-Tax Court implementation using a descriptive quantitative approach. The findings indicate that the e-Tax Court enhances time and cost efficiency, that restricting manual access helps accelerate implementation, and that a top-down policy effectively influences taxpayer behavior